Durability of SiO2–TiO2 Photocatalytic Coatings on Ceramic Tiles. (14th February 2014) - Sciancalepore, Corrado; Bondioli, Federica
Abstract : The aim of this investigation was the evaluation of the durability of photocatalytic sol–gel coating deposited on industrial ceramic tiles. In particular, the effect of substrate roughness on photocatalytic performance before and after different aging tests was determined. The results showed that the photodegradation process was clearly affected by the surface roughness of the substrate. In particular, the smoother surface had a higher photocatalytic activity, faster hydrophilicity but a lower durability to abrasion with respect to the matt surface.